The Polish Pension Reform of 2011 - Dybał, Mariusz (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The subject of the article is the interaction between pension funds and public finances in Poland in the period 1999-2012. The aim of this paper is to assess the pension reform of 2011 in the context of public finances. To achieve this objective, the author decided to implement the following research tasks: i) to determine the cause of the 2011 pension reform; ii) to present the objectives of the 2011 pension reform. The results of the research reveal that the main objective of the 2011 pension reform was to reduce the rate of growth of Poland’s public debt (an increase from 41.1% of GDP in 1999 to 52.8% of GDP in 2010), mainly by reducing the cost of introducing the second pillar while maintaining the neutrality of the solution to the pensions of the mandatory part of the pension system, as well as to stimulate the growth of retirement savings and thus of the overall replacement rates (reduction of the portion of contribution transferred to pension funds from 7.3% to 3.5%, by moving the rest of the retirement contribution to a newly created sub-account at the Social Security Institution).
Keywords: Polska; fundusze emerytalne; finanse publiczne; reforma emerytalna z 2011 r.